The Evolution of Mitral Valve Repair in India (Global Journal of Medical Research, 2020)
This is a review of the evolution of Mitral valve repair in India. Because of the prevalence of Rheumatic heart disease in India most of the techniques have been developed for this etiology. There was a need to adapt these techniques for the poor patients in order to reduce cost .As a consequence this review does not allude to the commercially available rings. Also this review does not cover the areas of ischemic and degenerative Mitral regurgitation because these techniques were not developed in India and only a couple of publications mention results in these two etiologies.
Keywords: rheumatic heart disease; mitral regurgitation; mitral valve repair